1989
DOI: 10.3354/meps056291
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and sedimentation of ice algae during and immediately after a bloom at the ice-water interface

Abstract: Sinking of pigmented particulate matter during and immediately after an ice algal bloom was studied in southeastern Hudson Bay at a 45 m deep station, using consecutive short-term deployments of sediment traps 30 m below the undersurface of the ice. Cell sinking and grazing by herbivores were assessed by measuring the vertical fluxes of chlorophyll a and phaeopigments. There were 2 peaks of cell sedimentation, a minor one during the first half of the bloom (mid-April) and a major one at the end of the bloom (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…Higher loss rates of chl a could be found in regions where the bulk of plant pigments was either found in FPC of large metazoans (Schnack 1985, Thibault et al 1999 or represented by sinking of phytoplankton in the ice zone (Sasaki & Hoshiai 1986, Tremblay et al 1989, Handa et al 1992). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher loss rates of chl a could be found in regions where the bulk of plant pigments was either found in FPC of large metazoans (Schnack 1985, Thibault et al 1999 or represented by sinking of phytoplankton in the ice zone (Sasaki & Hoshiai 1986, Tremblay et al 1989, Handa et al 1992). …”
Section: Discussionmentioning
confidence: 99%
“…Sasaki & Hoshiai 1986, Matsuda et al 1987, Tremblay et al 1989, massive sinking of ice-edge blooms (e.g. , Wilson et al 1986, Bathmann et al 1991, and sedimentation of algae from the spring-summer phytoplankton bloom (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Werner 2000, Fortier et al 2002 and, to a lesser extent, by sympagic fauna (Nozais et al 2001. The bulk of the ice algal biomass is mainly released into the water column at the time of spring ice melt (Tremblay et al 1989, Michel et al 1996, Fortier et al 2002. However, Melnikov (1998) suggested an export of material from the sea ice during ice growth, as a result of episodic brine drainage.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies looking at temporal changes in under-ice sinking fluxes of organic material have shown increasing sinking fluxes in response to the release of material from the sea ice during spring melt (Carey 1987, Tremblay et al 1989, Michel et al 1996, Fortier et al 2002. Melnikov (1998) suggested that ice algae in the western Weddell Sea are released from the ice during winter through brine drainage during ice growth.…”
Section: Seasonal Variations In Under-ice Sinking Fluxesmentioning
confidence: 99%
“…The total mean grazing impacts are in the same range as those imposed on melted-ice algae by pelagic sub-ice species (mainly Pseudocalanus spp. and Calanus glacialis) in spring (0.5 to 2.3%; Tremblay et al 1989). In the Antarctic, the daily grazing impact of ice krill Euphausia crystallorophias has been estimated to range between < l and 5% of the phytoplankton standing stock (Pakhomov & Periss~notto 1996).…”
Section: Grazing Impactmentioning
confidence: 99%